1982
DOI: 10.2136/sssaj1982.03615995004600060011x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Salinity on Soil Enzyme Activities

Abstract: Efforts were made to assess the levels of soil enzyme activities that have a specific role in the N, C, P, and S cycles of saline soils. Fieldmoist soil samples were treated with four rates of CaCl2, NaCl, and Na2SO4 solutions applied to produce electrical conductivity readings of saturation extracts (ECe) ranging up to 22 mmho/cm. The range of ECe values included threshold salinity levels associated with reduced yields of agronomic crops. After 7 d of equilibration, the following soil enzymes were assayed: am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
2
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(85 citation statements)
references
References 0 publications
1
80
2
2
Order By: Relevance
“…Therefore, we have only determined neutral and alkaline phosphatase activities since soil pH was 7.3. Catalase (Frankenberger and Bingham 1982), alkaline phosphatase (Garcia and Hernandez 1996), invertase, and urease (Omar et al 1994) activities were inhibited by increasing soil salinity. Similarly, we have observed that soil enzyme activities of control soil decreased proportionately by increasing salinity.…”
Section: Effect Of Inoculation On Plant Growth Under Salt Stressmentioning
confidence: 96%
“…Therefore, we have only determined neutral and alkaline phosphatase activities since soil pH was 7.3. Catalase (Frankenberger and Bingham 1982), alkaline phosphatase (Garcia and Hernandez 1996), invertase, and urease (Omar et al 1994) activities were inhibited by increasing soil salinity. Similarly, we have observed that soil enzyme activities of control soil decreased proportionately by increasing salinity.…”
Section: Effect Of Inoculation On Plant Growth Under Salt Stressmentioning
confidence: 96%
“…Katyal and Carter (1988) also found that increased hydrolysis rates were closely related with increasing time of submergence. Especially in a newly reclaimed tidal soils containing high salt content, urea hydrolysis can be delayed by the salts due to reduction in urease activity (Frankenberger and Bingham, 1982;Galstyn, 1960).…”
Section: Resultsmentioning
confidence: 99%
“…A salt-induced inhibition of phosphatase was observed by Frankenberger & Bingham (1982), who attributed the effect to osmotic desiccation or specific ion toxicity of soil microbes, or to a salting-out effect on the enzymes themselves. Alternatively, the results of our cross-habitat comparison can be explained by differences in the clay and organic matter content, which decreased as salinity increased.…”
Section: Discussionmentioning
confidence: 96%